1999
DOI: 10.1016/s0741-5214(99)70248-x
|View full text |Cite
|
Sign up to set email alerts
|

The postthrombotic syndrome in relation to venous hemodynamics, as measured by means of duplex scanning and strain-gauge plethysmography

Abstract: Most patients with severe PTS had a combination of deep and superficial reflux. Reflux in the deep proximal veins contributes significantly to the PTS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 23 publications
1
62
0
3
Order By: Relevance
“…30 Iliofemoral patency was noted in 65.9% of patients randomized to CDT compared with 47.4% of those who received conventional anticoagulant therapy, 30 but the prevalence of valvular reflux was similar in the 2 groups. 31 In contrast, Haenen et al 32 reported a significant positive correlation between increasing severity of PTS and prevalence of reflux in the proximal femoral vein (P<0.001), distal femoral vein (P<0.05), and popliteal vein (P<0.05). These investigators also noted that venous obstruction alone or in combination with reflux had no relation to the presence of severe PTS.…”
Section: Clinical Manifestations and Pathophysiology Characteristic Smentioning
confidence: 91%
“…30 Iliofemoral patency was noted in 65.9% of patients randomized to CDT compared with 47.4% of those who received conventional anticoagulant therapy, 30 but the prevalence of valvular reflux was similar in the 2 groups. 31 In contrast, Haenen et al 32 reported a significant positive correlation between increasing severity of PTS and prevalence of reflux in the proximal femoral vein (P<0.001), distal femoral vein (P<0.05), and popliteal vein (P<0.05). These investigators also noted that venous obstruction alone or in combination with reflux had no relation to the presence of severe PTS.…”
Section: Clinical Manifestations and Pathophysiology Characteristic Smentioning
confidence: 91%
“…In patients with deep vein reflux, the highest prevalence of valve incompetence was found in the FV and POPV [18]. Haenen et al [19] also demonstrated that advanced CVI was found in the FV and POPV with reflux, and reflux in the proximal deep veins significantly contributed to the development of PTS. These reports suggest that residual abnormalities in the proximal deep veins play a major role in the development of late PTS.…”
Section: Discussionmentioning
confidence: 96%
“…However, the proportion of patients with persistent venous occlusion was reported to be the same in patients with CEAP scores of C0-3 and C4-6. Haenen et al 8 showed reflux in the proximal deep veins to be associat ed with worse CEAP scores, but no such relation was shown for reflux in the superficial veins and distal deep veins and no relation was observed between vein noncompressibility or the combi nation of reflux and noncompressibility and PTS. In a second study, the same group showed super ficial venous reflux to be the most important risk factor for the onset of PTS symptoms, and 64% of patients with severe PTS were shown to have a combination of superficial and deep reflux.…”
Section: Tablementioning
confidence: 97%
“…[8][9][10] This review focuses on the diagnosis and risk determinants of PTS after DVT in adult patients.…”
Section: -4mentioning
confidence: 99%